Pleuroparenchymal sarcoidosis - A recognised but rare manifestation of disease. (2018) - Walker, S.; Adamali, H.; Bhatt, N.; Maskell, N.; Barratt, S.L.
Abstract: Pleural involvement is rare in sarcoidosis. The presence of a large symptomatic effusion in a patient with sarcoidosis should therefore prompt further investigation for an alternate aetiology. Here we present a case of confirmed pleuro-parenchymal sarcoidosis. We discuss the important differential diagnoses and review the current literature.